Clinical Profile and Outcome of Acute Pancreatitis in a Tertiary Health Care Center of Nepal - Gautam, Ajay Kumar; Dewan, Khus Raj; Shrestha, Rishab; K.C., Vijaya (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Acute pancreatitis is the inflammation of pancreatic parenchyma that can cause local and systemic manifestations. This study aimed to find the clinical profile and an outcome of acute pancreatitis among patients attending the Department of Gastroenterology in a tertiary care center. Methods A cross-sectional hospital based study comprising of 75 patients of acute pancreatitis, enrolled between August 2022 to June 2023. Clinical profile, complications and outcomes including in hospital mortality were studied. Revised Atlanta classification and modified CT severity index were used for diagnosis and classification. Data entry and analysis were done SPSS-17. Results Most common age group was 40-60 years (50.7%). The most common etiology was alcohol (46.7%) and almost all presented with abdominal pain (97%) and abdominal tenderness was present in 80%. Majority were mild pancreatitis (54.7%), followed by moderately severe (32%) and severe pancreatitis (13.3%). Factors that are significantly associated with prolonged stay at hospital and mortality were pleural effusion, necrotizing pancreatitis, acute kidney injury, BISAP score ≥ 2, high total leucocyte count, shock, severe CT severity score, multi organ dysfunction syndrome (MODS), acute respiratory distress syndrome (ARDS)(p≤0.05). Conclusions Acute pancreatitis is predominant in male gender and 40-60 years age group. It is associated with significant complications and mortality. Different parameters including high BISAP score, pleural effusions, acute kidney injury, leucocytosis and high CRP level on presentation were useful markers to predict outcome.